The making of Philip’s Macedonia: The archaeology of the Macedonian kingdom from the Persian Wars to the fall of Perdiccas III (c.510-359BC) - Laslett, L (2020)
This thesis aims to present and examine the archaeological material from the Macedonian kingdom between c.510 and 359 in order to provide an insight into Macedonian society, culture and religion at this time. This period is often neglected by scholars since it is bookended by the wealthy burials of the late sixth century, and Philip II’s rise to power and subsequent domination of the Hellenic world. Given this broad remit, the main body of the study is divided into four chapters, each of which deals with a discrete archaeological context or class of material.